Saneamiento básico y pluvial de la Ciudad Universitaria – UNSM - Bartra Pezo, Oscar (1998)
The University national of San Martin, before the increase of the population student, is has seen in the need of start Ia construction of them pavilions of classrooms the City University, for which must count with them services basic indispensable, as the water drinking, drain health and drainage rain. The present thesis work, presents the design of the services of drinking water, sanitary drainage and storm water drainage, in accordance with the requirements and technical standards specified for them. In chapter I, referred to the General aspects of the project, such as: background, location, importance, justification, objectives ~ enerales and specific, and an analysis of the problems of the University City. Chapter II, information for the elaboration of the thesis work, as it is: information about terrain, supplementary information, the latter presents a certificate of feasibility of E ~ apa-his Majesty, for the water connection pota...